Efficient ammonia synthesis over a Ru/La0.5Ce0.5O1.75 catalyst pre-reduced at high temperature. Issue 8 (29th January 2018) - Ogura, Yuta; Sato, Katsutoshi; Miyahara, Shin-ichiro; Kawano, Yukiko; Toriyama, Takaaki; Yamamoto, Tomokazu; Matsumura, Syo; Hosokawa, Saburo; Nagaoka, Katsutoshi
Abstract : A Ru/La0.5 Ce0.5 O1.75 catalyst pre-reduced at an unusually high temperature (650 °C) catalyses ammonia synthesis at a high rate under mild conditions. Abstract : Ammonia is an important feedstock for producing fertiliser and is also a potential energy carrier. However, the process currently used for ammonia synthesis, the Haber–Bosch process, consumes a huge amount of energy; therefore the development of new catalysts for synthesising ammonia at a high rate under mild conditions (low temperature and low pressure) is necessary. Here, we show that Ru/La0.5 Ce0.5 O1.75 pre-reduced at an unusually high temperature (650 °C) catalysed ammonia synthesis at extremely high rates under mild conditions; specifically, at a reaction temperature of 350 °C, the rates were 13.4, 31.3, and 44.4 mmol g −1 h −1 at 0.1, 1.0, and 3.0 MPa, respectively. Kinetic analysis revealed that this catalyst is free of hydrogen poisoning under the conditions tested. Electron energy loss spectroscopy combined with O2 absorption capacity measurements revealed that the reduced catalyst consisted of fine Ru particles (mean diameter < 2.0 nm) that were partially covered with partially reduced La0.5 Ce0.5 O1.75 and were dispersed on a thermostable support. Furthermore, Fourier transform infrared spectra measured after N2 addition to the catalyst revealed that N2 adsorption on Ru atoms that interacted directly with the reduced La0.5 Ce0.5 O1.75 weakened the NN bond and thus promoted its cleavage, which is the rate-determining step for ammonia synthesis. Our results indicate that high-temperature pre-reduction of this catalyst, which consists of Ru supported on a thermostable composite oxide with a cubic fluorite structure and containing reducible cerium, resulted in the formation of many sites that were highly active for N2 reduction by hydrogen.